Cryoballoon ablation for extrapulmonary vein targets. (January 2021) - Ling, Tian-You; Chen, Lin; Su, Wilber W.; Wu, Li-Qun
Abstract : Purpose of review: Cryoballoon catheter can create large and contiguous lesions with stable contact during ablation. It has proven to be well tolerated and effective in pulmonary vein isolation. But atrial arrhythmias, including atrial fibrillation, atrial tachycardia, and atrial flutter (AFL), also relate to many extrapulmonary vein targets. It is necessary to understand the current evidence for the use of cryoballoon ablation for targets outside of pulmonary veins. Recent findings: Studies have shown that the cryoballoon ablation can be used in extrapulmonary vein area, including left atrium roof, left atrial appendages, posterior left atrial wall, mitral isthmus, and right atrial appendage. The results indicate cryoballoon ablation is an effective and well-tolerated treatment option for the atrial arrhythmias in these locations outside of pulmonary vein when clinical necessary. Summary: The cryoballoon ablation can safely and effectively perform contiguous linear lesions, structure isolations, and local ablation for targets outside of the pulmonary veins.